(untitled) (Journal of Nepal Geological Society, 2000)
The environmental geological map of the Kathmandu Valley at a scale of 1:50,000 was prepared during a Technical CoOperation Project of the Department of Mines and Geology (DMG) of Nepal and the Federal Institute for Geosciences and Natural Resources, Germany. This map is meant to draw attention to the natural environmental risks and hazards, as well as to recommend measures for the protection of important natural resources in the Kathmandu Valley. This thematic map is addressed mainly to governmental agencies and consultants, who can use the map as a database for planning purposes, especially for planning new settlement areas and various types of infrastructure. The map shows the locations of clay, sand, limestone, groundwater, and forest. These resources are very important for the economic development of the Kathmandu Valley. They need protection against the haphazard growth of settlement areas. In the case of mining, environmentally sound methods with monitoring and supervision is recommended. Areas to be considered for agricultural use (rain-fed or irrigation) are also delineated. The map also shows areas of geological hazards and related environmental problems from floods, landslides, and liquefaction of soils. Pollution caused by human activities, such as river pollution, and areas of uncontrolled landfills are also indicated. Pollution of the Bagmati River and its tributaries and the resulting degradation of water quality is a burning issue in the Kathmandu Valley. Rapid urbanisation and increasing volume of industrial and municipal wastes have drastically changed the sacred river into an open sewer. The map has already been used for the general assessment of the environmental geological risks in 27 new settlement areas in the Kathmandu region. This study realised that there is a conflict with other competing interests. e.g., the interests of the landowners. The promotion and implementation of environmentally sound recommendations is very complicated and politically sensitive. Nevertheless, these difficulties should not discourage the planners, because the promotion of environmentally sound aspects is for the long-term benefit of the whole population of the area.